Evaluation of different cryoprotectant combinations in vitrification and slow freezing for ovarian tissue preservation in domestic cats - Ribeiro, Rayane Brandão (2025)
Over the past decade, increased hunting and habitat disturbance have significantly impacted the endangered population within the Felidae family. Recognising this, it becomes imperative to implement strategies aimed at mitigating this concerning conservation scenario. For this, female fertility preservation is crucial in this context, and studies concerning this field are still scarce. In the realm of cryopreservation, prevalent methods involve slow freezing (SF) and vitrification (V). This study aimed to evaluate various cryoprotective combinations for V or SF processes applied to domestic cat ovarian tissue. Twenty ovaries from 10 healthy cats were dissected, and cortical regions were sectioned into eight fragments measuring 3 mm3 each. These fragments were randomly allocated to three different treatment groups for V (V1, V2 and V3) or SF (SF1, SF2 and SF3). Each group employed solutions with varying concentrations of DMSO, EG and either trehalose or sucrose. The assessment included histological evaluation, follicle counting, immunohistochemical analysis of proliferative activity, and ultrastructural examination. The results demonstrated that the V1 protocol—composed of an equilibration solution with 10% DMSO, 10% EG and 0.1 M trehalose, followed by a V solution with 20% DMSO, 20% EG and 0.1 M trehalose—proved most effective. This combination best preserved follicular morphology, reduced degeneration, supported follicle proliferation and maintained favourable ultrastructural integrity compared to other treatments. These findings provide a valuable foundation for improving fertility preservation in domestic cats, with potential applications for endangered felid conservation programs.